Measuring group switching in the European Parliament: Methodology, data and trends (1979-2009) - Evans, Ana Maria (2012)
Party group switching in the European Parliament (ep), where parliamentarians individually or collectively switch from one party group to the other, is a well-known contributor to the volatility of the ep party system. We present a new dataset that contains party group information on all meps from 1979 to 2009. As a first step to a more comprehensive analysis of the phenomenon of party group switching in the ep we describe characteristics of all switches that have occurred in these six legislatures, with a focus on the trends across time, variety between member states, party groups, and ideological party families.